Aplicativo móbile para ensino de histórias bíblicas para crianças surdas - GONÇALVES, Larissa Keller de Souza (109, 2020)
A lei de direito à informação garante ao indivíduo o direito do conhecimento de seus interesses pessoais e coletivos por meio dos órgãos públicos. Porém, isso não acontece por inúmeros fatores . Apesar dos grandes avanços , um dos conhecimentos mais inacessíveis aos surdos é a bíblia. A LIBRAS, Língua Brasileira de Sinais é bem mais simples se comparada as línguas faladas. E para as crianças a informação e acessibilidade é ainda mais limitada.

Given the vast amount of information and technology that surrounds us, even today many people do not have effective access to much of it. This happens due to physical limitations that many of them have, such as deafness, which is not supplied through digital accessibility. The right to information law guarantees individuals the right to know their personal and collective interests through government agencies. However, we see that this does not happen due to numerous factors. Despite the great advances, one of the most inaccessible knowledge to the deaf is the Bible. Many deaf people are not able to have such a clear understanding of Portuguese because this is not their first language and because many documents and information have a more complex language, such as the Bible. Libras, Brazilian Sign Language, is much simpler compared to spoken languages, so it is not easy for a deaf person to understand written Portuguese. Although some deaf people are able to verbalize and even do lip reading, unfortunately this is not the reality of the majority. For children, information and accessibility is even more limited, as they need a playful and easily understood learning process, because of that, the deaf child audience is still a great challenge in terms of religious education. Due to all of these issues, the proposal for an application that will help deaf children learn in an accessible and recreational way will be presented in this undergraduate paper. This app called Finger Story is just a prototype, however it aims to be a gamification game where the child will be able to read stories from the Bible, answer activities on the topic learned, win prizes and personalize the avatar with items from the online store. Thus, the application will be able to contribute with the lack existing to the deaf public to the child bible teaching as it will also bring fun to these children.

Given the vast amount of information and technology that surrounds us, even today many people do not have effective access to much of it. This happens due to physical limitations that many of them have, such as deafness, which is not supplied through digital accessibility. The right to information law guarantees individuals the right to know their personal and collective interests through government agencies. However, we see that this does not happen due to numerous factors. Despite the great advances, one of the most inaccessible knowledge to the deaf is the Bible. Many deaf people are not able to have such a clear understanding of Portuguese because this is not their first language and because many documents and information have a more complex language, such as the Bible. Libras, Brazilian Sign Language, is much simpler compared to spoken languages, so it is not easy for a deaf person to understand written Portuguese. Although some deaf people are able to verbalize and even do lip reading, unfortunately this is not the reality of the majority. For children, information and accessibility is even more limited, as they need a playful and easily understood learning process, because of that, the deaf child audience is still a great challenge in terms of religious education. Due to all of these issues, the proposal for an application that will help deaf children learn in an accessible and recreational way will be presented in this undergraduate paper. This app called Finger Story is just a prototype, however it aims to be a gamification game where the child will be able to read stories from the Bible, answer activities on the topic learned, win prizes and personalize the avatar with items from the online store. Thus, the application will be able to contribute with the lack existing to the deaf public to the child bible teaching as it will also bring fun to these children
Mobile application for teaching bible stories to deaf children
Keywords: Crianças; aplicativos móveis; Informação e Comunicação